Beyond Oneness and Difference : Li and Coherence in Chinese Buddhist Thought and Its Antecedents - Ziporyn, Brook, 1964- (Book collections on Project MUSE., 2013)
"Continues the author's discussion of the development of the Chinese philosophical concept Li, concluding in Song and Ming dynasty Neo-Confucianism"--Provided by publisher